Holt-Oram Syndrome: When hand deformity leads to diagnosis of congenital heart disease - Dmowski, Daniel; Świda, Michał; Bazarewicz, Jakub; Kubuj, Cezary; Adaśko, Grzegorz; Mazur, Urszula; Siwik, Marcin; Michalska, Anna; Ogonowska, Paulina; Waszak, Julia (Quality in Sport, 2025)
Introduction: The following review paper is an in-depth analysis of a rare condition called Holt-Oram syndrome. It explores the underlying mechanisms of the condition’s pathophysiology, its diverse clinical manifestations, symptoms, and the challenges associated with diagnosis and treatment. Materials and methods: A thorough review of the extant literature was conducted using the PubMed and Google Scholar databases. The following keywords were used: „Holt-Oram Syndrome”, „HOS”, „TBX5 mutation”, „Heart-Hand Syndrome”, „congenital heart defect”, „cardiac-limb syndrome” Conclusions: Holt–Oram syndrome is a genetic disorder caused by mutations in the TBX5 gene, typically inherited in an autosomal dominant manner. However, de novo mutations have also been reported in some cases. A hallmark of this syndrome is upper limb malformation, most commonly affecting the radial ray. In approximately 70% of patients, congenital heart defects co-occur with limb abnormalities. The clinical spectrum of Holt–Oram syndrome is highly variable, ranging from mild anatomical changes to severe functional impairments. The diagnosis cannot be confirmed or ruled out using current diagnostic criteria, and confirmation requires molecular analysis of the TBX5 gene. This is because the picture may sometimes be incomplete, or the phenotype may overlap with other similar conditions. The management of Holt–Oram syndrome is highly individualized and closely tailored to the specific clinical manifestations present in each patient and also often requires the involvement of many specialists.